Literature Review: Analisis Faktor Risiko Penyebab Terjadinya Diabetes Melitus pada Remaja - Putri Hervilanti; Nur Alam Fajar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Diabetes Mellitus is a non-communicable disease whose prevalence continues to increase every year. The number of teenagers diagnosed with diabetes mellitus increases every year throughout the world, so prevention efforts are needed to reduce the number of diabetes mellitus in teenagers. The author of this article aims to identify risk factors that cause diabetes mellitus in adolescents. This research is a systematic review research with an article search methodology using Google Scholar and Pubmed searches published in 2019-2024 with the keywords Factors/Risk Factors/Determinas as risk of diabetes in adolescents where there are 10 research articles identified and it is known that there are factors- factors associated with diabetes risk. The risk factors found were family history, smoking habits, gender, knowledge, diet, physical activity and obesity. This is the basis for determining policies to prevent and control diabetes mellitus by providing education to teenagers and families, for example exercising regularly, reducing sweet foods, and consuming vegetables and fruit every day.